Novel Drugs Targeting the SARS-CoV-2/COVID-19 Machinery - Sternberg, Ariane; McKee, Dwight L.; Naujokat, Cord (Current Topics in Medicinal Chemistry, 2020)
Like other human pathogenic viruses, coronavirus SARS-CoV-2 employs sophisticated macromolecular machines for viral host cell entry, genome replication and protein processing. Such machinery encompasses SARS-CoV-2 envelope spike (S) glycoprotein required for host cell entry by binding to the ACE2 receptor, viral RNA-dependent RNA polymerase (RdRp) and 3-chymotrypsin-like main protease (3Clpro/Mpro). Under the pressure of the accelerating COVID-19 pandemic caused by the outbreak of SARS-CoV-2 in Wuhan, China in December 2019, novel and repurposed drugs were recently designed and identified for targeting the SARS-CoV-2 reproduction machinery, with the aim to limit the spread of SARS-CoV-2 and morbidity and mortality due to the COVID-19 pandemic.
Keywords: 3Clpro